Characterization of Coronary Risk Factors in Workers at the Guillermo Domínguez López Hospital in Las Tunas - Alián Pérez Marrero; Jorge Enrique Labrada Cruz (Revista Finlay, 2024)
Foundation: acute coronary syndromes constitute a health problem due to their high morbidity and mortality. It would be reasonable to assume that health workers take care of and control their own coronary risk factors, however, research results show that this is not always the case. Objective: to characterize coronary risk factors in workers at the Guillermo Domínguez López General Teaching Hospital in Las Tunas. Method: a descriptive cross-sectional study was carried out at the Guillermo Domínguez López General Teaching Hospital in Las Tunas between December 2019 and December 2022. The study population was 912 workers and the sample was 200. It was a probabilistic, simple random sampling divided into two groups: A (with acute coronary syndrome) and B (without acute coronary syndrome). The following variables were analyzed: age, sex, coronary risk factors. The information was obtained from clinical records and analyzed in percentage, mean, standard deviation and the z statistic to obtain the influence of risk factors on the disease. Results: the average age of group A: 56.5 (±5.03), group B: 46.4 (±11.33) years with a predominance of the male sex (54.5 %). The predominant risk factors were: sedentary lifestyle (57 %), smoking (36.5 %) and high blood pressure (34 %). Those with the greatest influence were: a history of ischemic heart disease, vascular disease, abdominal obesity (z: 0.99), diabetes mellitus (z: 0.92) and arterial hypertension (z: 0.70). Conclusions: coronary syndrome predominates in the fifth decade of life and is more common in males.